Sudut Pandang Hermeneutik Hans-Goerg Gadamer - Yefri Yandri (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study discusses Hans-Georg Gadamer's philosophical hermeneutics as an important approach to understanding texts and human experience. Starting from Gadamer's critique of positivism and methodological objectivism, this paper asserts that understanding is not merely a technical process, but rather an ontological event that is always bound to history, language, and tradition. Through key concepts such as fusion of horizons (Horizontverschmelzung), prejudice (Vorurteil), and historical effect (Wirkungsgeschichte), Gadamer shows that the meaning of a text is not static, but rather continues to live in a dialogue between the text and its readers. This study uses a qualitative approach with a literature review method to analyze Gadamer's major works and relevant secondary literature. The results of the study show that Gadamer's hermeneutics has made a significant contribution in shifting the understanding of hermeneutics from a methodological framework to a dialogical, reflective, and contextual philosophical approach, making it relevant to the study of philosophy, humanities, and contemporary religious studies.